2017
DOI: 10.1021/acssuschemeng.7b02582
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Kraft Lignin with Hydrogen Peroxide and its Application as a Dispersant for Kaolin Suspensions

Abstract: Lignin is an underutilized byproduct of pulping and cellulosic ethanol production plants. However, if utilized efficiently, it can facilitate the development of sustainable processes. In this work, oxidized kraft lignin (OKL) was prepared via treating kraft lignin (KL) with hydrogen peroxide, an environmentally friendly and industrially attractive oxidizing agent, under alkaline conditions. The oxidized kraft lignin with a carboxylate group content of 1.53 mequiv/g was obtained under the optimal oxidation cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 57 publications
6
64
2
Order By: Relevance
“…There are several oxidants that can be employed for the oxidation of lignin and one way to differentiate them is by strength: strong and mild . Strong oxidants, such as hydrogen peroxide, will disrupt the aromatic ring . Mild oxidants, such as air, oxygen, and nitrobenzene, keep the aromatic ring intact.…”
Section: Depolymerization Of Ligninmentioning
confidence: 99%
“…There are several oxidants that can be employed for the oxidation of lignin and one way to differentiate them is by strength: strong and mild . Strong oxidants, such as hydrogen peroxide, will disrupt the aromatic ring . Mild oxidants, such as air, oxygen, and nitrobenzene, keep the aromatic ring intact.…”
Section: Depolymerization Of Ligninmentioning
confidence: 99%
“…It is reported that hydrogen peroxide generally decomposes the phenolate group of lignin, whereas it induces the carboxylate group into lignin. 42,240,241 It was reported that the majority of hydrogen peroxide molecules was utilized for the partial decomposition of the lignin structure by the bond cleavage of lignin's ether bonds. 240 Fig.…”
Section: Oxidationmentioning
confidence: 99%
“…42,240,241 It was reported that the majority of hydrogen peroxide molecules was utilized for the partial decomposition of the lignin structure by the bond cleavage of lignin's ether bonds. 240 Fig. 12 shows the mild oxidation by using different sources of lignin and oxidizing reagents.…”
Section: Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…As oxidation is a kind of chemical modification method of lignin, the oxidization products of lignin can be obtained under certain reaction conditions and be utilized in some aspects [11,12]. For example, kraft lignin could be oxidized by H 2 O 2 , and the oxidization products were employed as a dispersant for kaolin suspensions [13]. Besides oxidization, other modification methods of lignin are useful as well [14].…”
Section: Introductionmentioning
confidence: 99%